Desenvolvimento de aplicativos como uma ferramenta de aprendizagem na área de matemática - Handa, Rene Augusto (2017)
In this work we present a detailed construction of the following mobile applications: Que Dia Foi which uses mathematical concepts of divisibility and congruence to determine the day of the week in which a date occurred and Cálculo de Áreas, which uses the Shoelace Theorem to determine the area of a region defined by coordinates collected by GPS. The development of these mobile applications require skills that are common to mathematical thinking, as well as the mathematics concepts inherent in applications. In this way we aim to offer an option to project-based learning initiatives, which is the development of applications for mobile devices with Andriod operating system, through the online platform MIT App Inventor 2. The MIT App Inventor 2 platform allows to program by fitting blocks, that is, more visual and with a number of features available.